Adults blink more deeply: a comparative study of the attentional blink across different age groups. Issue 2 (29th December 2016) - Russo, Natalie; Kates, Wendy R.; Shea, Nicole; LeBlanc, Megan; Wyble, Bradley
Abstract: The attentional blink (AB) is thought to help the visual system parse and categorize rapidly changing information by segmenting it into temporal chunks, and is elicited using Rapid Serial Visual Presentation. It is reflected in a decrease in accuracy at detecting the second of two targets presented within 200–500 ms of the first, and its development appears to be protracted on tasks that require set‐shifting. Here, younger ( M  =   8.5 years) and older ( M  =   12.8 years) children and adults ( M  =   19.13 years) completed a simple AB task with no set‐shift requirement in which participants detected two letters in a stream of numbers presented at a rate of 135 ms/item. In addition to assessing the developmental course of the AB on this simple task, we also assessed temporal order errors, or swaps. The AB and its associated characteristics are present in both groups but developmental differences were noted in the depth of the AB, and the presence or absence of lag‐1 sparing. These developmental changes were explained by changes in a single parameter, inhibition, using the eTST model, which suggests that the AB is an adaptive function of the visual system. Abstract : The attentional blink (AB) is commonly thought to reflect a limitation on the rate of information processing, since it shows that people have trouble identifying two targets when they are presented closely in time. However, another possibility is that the attentional blink reflects an adaptive attentional mechanism that allows for temporal chunking of incoming visual information. This theory predicts that the AB should increase during development, as this attentional system matures. Here, using a simpler design, we find that the AB depth increased with increasing age across childhood, adolescence and into adulthood (top of Figure). Temporal order errors also decreased as the AB increased (bottom of Figure) suggesting a tradeoff. Both of these results could be simulated by the eSTST model of the attentional blink (Wyble et al., 2009) through an increase in the strength of inhibitory control with age.